Comunicación interdepartamental y liderazgo en trabajadores de la asociación de Exportadores - Adex - Galindo Palomino, Dany Luis (Universidad Nacional Federico Villarreal, 2013)
A correlational research interdepartmental communication between workers and leadership in ADEX 2013 period with the overall aim of establishing whether there was a relationship between the two variables. It also sought to establish whether the level of interpersonal communication correlates with three types of leadership: transformational, transactional and corrective/avoider. Questionnaire analysis of interdepartmental communication and the Multifactor Leadership Questionnaire (MLQ Form 5X Short ) by Bass and Avolio: two instruments to measure both variables were applied. The results show that there is a relationship between interdepartmental communication and leadership on workers in ADEX. Also, it was found that interdepartmental communication correlates with transformational leadership and corrective / avoidant leadership and not with respect to transactional leadership. It is recommended to research to deepen the relationship between inter-and intra-departmental communication.

Se realizó una investigación correlacional entre comunicación interdepartamental y liderazgo en trabajadores de ADEX, periodo 2013 con el objetivo general de establecer si existía relación entre ambas variables. Así mismo se procuró establecer si el nivel de comunicación interpersonal correlaciona con tres tipos de liderazgo: transformacional, transaccional y correctivo/evitador. Se aplicaron dos instrumentos para medir ambas variables: Cuestionario de análisis de la comunicación interdepartamental y el Cuestionario Multifactorial de Liderazgo (MLQ Forma 5X Corta) de Bass y Avolio. Los resultados encontrados demuestran que existe relación entre comunicación interdepartamental y liderazgo en los trabajadores de ADEX. Así mismo, se encontró que la comunicación interdepartamental correlaciona con liderazgo transformacional y liderazgo correctivo/evitador y no con respecto a liderazgo transaccional. Se recomienda realizar trabajos de investigación que profundicen la relación entre comunicación inter e intradepartamental
Keywords: Comunicación; Interdepartamental; Liderazgo; Trabajadores; Asociación; Exportadores; Adex; https://purl.org/pe-repo/ocde/ford#5.01.00